Simulation study of deep eutectic solvent-based biogas upgrading process integrated with single mixed refrigerant biomethane liquefaction - Junaid Haider; Muhammad Abdul Qyyum; Bilal Kazmi; Imran Ali; Abdul-Sattar Nizami; Moonyong Lee (Biofuel Research Journal, 2020)
Deep eutectic solvents (DESs) comprise ChCl/urea, in combination with water, have been considered in removing acid gases (CO2 and H2S) from biogas. The evaluation of DES for biogas upgrading at relatively high pressure (i.e., >8.0 bar) has not been reported before. The aqueous DES performance has also not been analyzed compared to conventional amines-based solvent (MEA) and ionic liquid (IL). To the best of our knowledge, this is the first study that presents the integration of DES-based biogas upgrading with a mixed refrigerant liquefaction process to facilitate the safe and economical transportation of biomethane over long distances. The biogas considered in this study consisted of 60% CH4, 39% CO2, and 1% H2S. The aqueous ChCl/urea (70 wt%) results in biomethane with ≥99.0 wt% purity and ≥97.0 wt% recovery. Then, this biomethane was liquefied with ≥90% liquefaction rate. Based on the results obtained herein, overall capital, operating, and total annualized cost savings of 2.8%, 25.82%, and 14.26% were achieved using the 70% DES-based integrated process in comparison with the MEA-based integrated process. Whereas 1.41%, 16.85%, and 8.71% capital, operating, and total annualized costs could be saved in comparison with the IL (i.e., [Bmim][PF6])-based integrated process. It could be deduced that the overall cost of the biomethane value chain can be reduced using the proposed approach.